PROFIL KASUS PENDERITA PROLAPSUS UTERI DI POLIKLINIK OBSTETRI DAN GINEKOLOGI RSUP SANGLAH DENPASAR PERIODE APRIL 2015 – MARET 2016 - Anak Agung Istri Ayu Detritha Sarasmarth; I Nyoman Gede Budiana (Universitas Udayana, 2020)
Pelvic organ prolapse is a condition which pelvic organ have falled or slipped from normal anatomical position in the form of protrusion into the vagina even got out of the vagina due to dysfunction of the pelvic floor muscles, fascia and ligaments Endopelvic. Pelvic organ that may experience prolapse includes the uterus (uterine prolapse = PU). Descriptive method with retrospective cross-sectional design is used in this study using secondary data such as medical records of patients in Sanglah Hospital in the period April 2015 until March 2016 to see the picture of the characteristics of patients with PU. With the total sampling method that produces 26 samples. Data was analyzed descriptively using SPSS.Based on medical records of uterine prolapse patients at Sanglah Hospital in the period April 2015 to March 2016 (26 cases), the majority of cases discovered at the age of 61-80 years as many as 13 people (50%), according to the number of parity> 3 as many as 20 people (76.9% ), according to the work of as many as 15 people (57.7%) as a Housewife (IRT), and menopausal status known 22 people (84.6%) had experienced menopause. Based on the degree of uterine prolapse, most were in stage III as many as 14 people (53.8%). Based therapy, as many as 20 people (76.9%) choose operative action. Keywords : Uterine prolapse, age,parity, menopausal status, therapy